2021
DOI: 10.1002/ece3.7822
|View full text |Cite
|
Sign up to set email alerts
|

Species distribution models for predicting the habitat suitability of Chinese fire‐bellied newt Cynops orientalis under climate change

Abstract: Global climate change is occurring at an unprecedented rate, which may have significant influences on all levels of biodiversity from genes to ecosystems (Grünig et al., 2020). The Fifth Assessment Report (AR5) produced by the Intergovernmental Panel on Climate Change (IPCC) states that global warming is expected to continue with the average temperature of earth increasing by 0.3-4.5℃ by 2,100 compared with 1986-2005. Climate change has caused substantial geographical distribution changes in a wide

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…Bioclimatic factors such as precipitation and temperature are especially likely to influence ecological processes and biological functioning in amphibians (Olden & Rooney, 2006). Variables related to extreme environmental conditions (precipitation of the warmest quarter and mean temperature of the wettest quarter) emerged as important in explaining the turnover in GC endemic amphibians, similar to previous studies on amphibians (Bolitho & Newell, 2022; Guo et al, 2021). Precipitation of the wettest quarter has also been linked to both tree diversity and water availability (Soares & Brito, 2007).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Bioclimatic factors such as precipitation and temperature are especially likely to influence ecological processes and biological functioning in amphibians (Olden & Rooney, 2006). Variables related to extreme environmental conditions (precipitation of the warmest quarter and mean temperature of the wettest quarter) emerged as important in explaining the turnover in GC endemic amphibians, similar to previous studies on amphibians (Bolitho & Newell, 2022; Guo et al, 2021). Precipitation of the wettest quarter has also been linked to both tree diversity and water availability (Soares & Brito, 2007).…”
Section: Discussionsupporting
confidence: 85%
“…Other than geographic distance, precipitation of the warmest quarter, mean temperature of the wettest quarter, and mean diurnal temperature range best predicted species turnover. Several previous studies have found one or more of these bioclimatic variables to be important in explaining the observed distribution and richness patterns of amphibians (Ballesteros-Barrera et al, 2022;Barrett et al, 2014;Guo et al, 2021). Bioclimatic factors such as precipitation and temperature are especially likely to influence ecological processes and biological functioning in amphibians (Olden & Rooney, 2006).…”
Section: Discussionmentioning
confidence: 98%
“…For example, precipitation of warmest quarter was found among the most impor-tant environmental factors in explaining the distribution of many amphibian species in previous studies [78][79][80]. Whilst the response curve of precipitation of the warmest quarter for urban areas is broadly in line with the previous study predicting habitat suitability of amphibians in southern China [79], the decreased roadkill risk at precipitation greater than approximately 1000-1200 mm might also be related to the decrease in the number of derived roadkill samples in areas known for a hot, humid climate in the southern region of Taiwan island [79]. In contrast to road density, which represents the 'hazard' component of vehicle collision risks, environmental variables linked to species presence represent the 'exposure' component [33].…”
Section: Discussionmentioning
confidence: 97%
“…However, the combination of climate change and overfishing has resulted in a decline in fish resources and a gradual reduction in biodiversity [37][38][39]. This has the potential to alter the spatial distribution as it affects the community structure and agglomeration effect [40][41][42]. To protect and restore fish stocks and manage fishery ecosystems in the Beibu Gulf, the highly suitable areas during the withered and high-water periods can be superimposed over the gradient-suitable area of the MaxEnt model.…”
Section: Discussionmentioning
confidence: 99%